Does the small business program benefit self-employed workers? - RODRIGUEZ RAMIREZ, Rony Rodrigo Maximiliano (KDI School, 2018)
Do social programs lead to higher incomes for self-employed workers? In many Latin American countries, governments have been implementing a diverse set of social programs to improve the living standards of the target groups. I study the policy shift of the current Government of Nicaragua that started in 2012 towards self-employed workers with the implementation of the Small Business of the Family Economy (SBFE) program of the Ministry of Family Economy, Community, Cooperative, and Associative. This paper aims to quantify the impact of the SBFE program on self-employed workers’ income. I use data from the Living Standards Measurement Survey (LSMS) implemented by the National Institute of Development Information of Nicaragua. The results suggest that the program has a positive effect on the income of self-employed workers. Specially, those with low educational attainment and in manufacturing, hotels and restaurants sectors are more likely to benefit from the program. In terms of gender, females seem to benefit more than males from the program implementation.
Thesis(Master) --KDI School:Master of Development Policy,2018